Mental imagery in anxiety disorders - Hirsch, C; Holmes, E (2007)
Distressing mental images are common in anxiety disorders and have recently been found to have an important role in the maintenance of anxious problems. For example, in post-traumatic stress disorder (PTSD) the hallmark feature is the presence of recurrent sensory images of a past trauma, known as 'flashbacks'. These flashbacks comprise the key information that needs to be addressed in cognitive-behavioural therapy (CBT) to treat this disorder successfully. Another example of imagery having a key role in maintaining clinical problems is social phobia. Clients with social phobia are concerned about how they come across to other people. They spontaneously generate distorted negative images of themselves performing poorly in social situations. These idiosyncratic images represent the clients' key fears. The images are often stereotyped, with the same imagery being generated across a range of anxiety-provoking social situations. When the images are generated, the clients feel more anxious and believe that others can see their symptoms of anxiety. Research that has manipulated self-imagery in social phobia has shown that negative imagery has a key role in maintaining the disorder. Anxious imagery often relates to a memory of an earlier aversive or traumatic situation, but the clients experience it as if it is happening in the 'here and now' and that the imagery is a true representation of how they appear to others. Clinicians need to assess and target imagery in the psychological treatment of anxiety disorders. CBT has techniques to target imagery and the associated traumatic memories across anxiety disorders. © 2007 Elsevier Ltd. All rights reserved.